Consumers’ Attitudes Toward Counterfeit Automotive Parts - Oskar, Dimas Perdana (Jurnal Pendidikan Tambusai, 2022)
The main objective of this research is to track the consumers’ behavioral intention toward counterfeit automotive parts especially the fast moving automotive parts. This objective was accomplished by employing Fishbeins’ Multi-Attribute Model (introduced by Martin Fishbein in 1967) and Theory Reasoned Action (Fishbein and Ajzen, 1975). Using a non-probability sampling method, a purposive sampling method of 145 respondents was drawn. The research held especially in the unauthorized workshop or unauthorized automotive parts’ store in Yogyakarta. Respondents were asked to fill the self-completion questionnaire that was design in Five-Points Likert Scales. The data collected were analyzed by using Factor analysis, Corrected Item-Total Correlation, linear regressions, and multiple regressions. The result shows us that Behavioral intention (BI) is significantly influenced by attitude toward counterfeit automotive parts (Ao) and Behavioral intention (BI) is also significantly influenced by attitude toward the behavior of buying counterfeit automotive parts (Ab). On contrary, Behavioral intention (BI) toward buying the counterfeit automotive parts is not significantly influenced by Subjective norm (SN).